Aarhus Kunstmuseum : Katalog Over Skulpturer, Objekter og Keramik. (Aarhus : Aarhus Kunstmuseum, 1985)
Adler Petersen, Lene ; Andersen, Clara ; Arp, Hans (Jean) ; Baekhoj, Poul ; Beuys, Joseph ; Bille, Ejler ; Bindesboll, Thorvald ; Bissen, Christian Gottlieb Vilhelm ; Bissen, Hermann Wilhelm ; Bjerg, Johannes C. ; Boggild, Mogens ; Braase, Ib ; Brogger, Stig ; Chadwick, Lynn ; Christensen, Kirsten ; Reinhoud ; Dalsgaard, Sven ; Eickhoff, Gottfred ; Find, Ole ; Fischer, Adam ; Fischer, Egon ; Fjeldskov, Niels Valdemar ; Funch, Edgar ; Garde, Tora ; Gauguin, Jean ; Geertsen, Ib ; Gernes, Paul ; Ghermandi, Quinto ; Gregersen, Emil ; Gudmundsen-Holmgreen, jorgen ; Guttormsen, Niels ; Hamada ; Hammershoi, Svend ; Hansen, Poul ; Hansen, Svend Wiig ; Hanssen, Erik Gram ; Hasselriis, Louis ; Hauptmann, Sven ; Have, Henrik ; Hedegaard, Johannes ; Heerup, Henry ; Heiberg, Kasper ; Heide, Erik ; Henning, Gerhard ; Hjort, Hans ; Hjort, Luritz ; Holmskov, Helge ; Irminger, Ingeborg Plockross ; Jacobsen, Robert ; Jensen, Helge ; Jensen, Soren Georg ; Jerichau, Jens Adolf ; Jorgensen, Borge ; Jorn, Asger ; Kähler, Herman A. ; Keil, August ; Kiaerskou, Paul ; Kienholz, Edward ; Köpcke, Arthur ; Kramer, Per ; Krojer, Tom ; Kroyer, Peder Severin ; Larsen, William P. ; Liisberg, Hugo ; Louis-Jensen, Peter ; Lütken, Per ; Mancoba, Sonja Ferlov ; Marini, Marino ; Meden, Max ; Mogensen, Thorals ; Munch-Petersen, Lisbeth ; Munch-Petersen, Ursula ; Neble, Per ; Nellemose, Knud ; Nielsen, Jais ; Nielsen, Kai ; Nielsen, Morten ; Noack, Astrid ; Norgaard, Bjorn ; Nyholm, Erik ; Olafsson, Sigurjon ; Olafsson, Tove ; Oldenburg, Claes ; Orskov, Willy ; Parc, Julio Le ; Poulsen, Christian ; Ragoczy, Laura ; Rasmussen, Peder ; Rasmussen, Rasmus ; Rasmussen, Ulf ; Rathsack, Svend ; Reistrup, Frederik Karl Kristian ; Reistrup, Hansen ; Salto, Axel ; Siesbye, Alev ; Sondergaard, Poul ; etc.
boek